2021
DOI: 10.1021/acs.jchemed.1c00383
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Periodic Table to Kichwa: An Ecuadorian Native Language

Abstract: Minorities' languages face transformation processes and struggle against many social and linguistic limitations. Education systems in these languages are not optimal to promote the teaching of ancestral knowledge and scientific research. This is the case of Kichwa, an Ecuadorian native language that more than half-million people speak with different variations among the country. Kichwa lacks science tools to respond to educational needs, unleashing the gradual loss of intercultural diversity. The adaptation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%